The Model of Citra Pratama Employee Performance - Muhammad Syafri (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this research is to analyze the influence of work conflict on employees' performance at CV Citra Pratama branch office in Tasikmalaya. A descriptive method with a quantitative approach was utilized for the study. The sample size consisted of 30 employees from CV Citra Pratama branch office located in Tasikmalaya. Questionnaires and literature review were employed as data collection techniques for this study. Correlation coefficient test, coefficient of determination test, and simple linear regression analysis were applied to analyze the collected data. The analysis results showed that the correlation coefficient was 78.5%; the coefficient of determination was 61.6%; and the regression equation was Y = -9.818 + 1.155X. According to the hypothesis testing using a t-test, it was revealed that the t-arithmetic is greater than the t-table, thus we accept the null hypothesis with a significance of 0.000 < 0.04. The finding of this study is that work conflict has an impact on employee performance in CV. Citra Pratama Cabang Tasikmalaya, meaning that the higher the work conflict, the lower the employee performance.